Gastric cancer mortality in Sergipe (2013-2023): A spatial and temporal analysis (Research, Society and Development, 2025)
Introduction: Deaths from gastric cancer constitute a serious public health issue in Brazil, involving high morbidity and mortality rates, especially in underserved regions. Regional disparities in access to diagnosis and treatment contribute to variations in survival rates. This study aims to analyze spatial, temporal, and epidemiological patterns of mortality due to gastric neoplasms in Sergipe between 2013 and 2023. Methods: A retrospective observational study was conducted using mortality data from official health databases (DATASUS). The study included deaths within the specified period and assessed variables such as age, sex, municipality of residence, education level, and time to treatment initiation, drawing comparisons with data from the literature. Results: The findings indicate significant variations in gastric cancer mortality across municipalities over the years, with noticeable changes especially after the COVID-19 pandemic. Delays in diagnosis and treatment initiation were associated with higher mortality rates. Additionally, inequalities in access to specialized services were observed, highlighting the need for health policies aimed at early detection and treatment efficiency. Conclusion: The study underscores the importance of addressing regional inequalities in cancer care in Sergipe. There is an urgent need to strengthen early detection programs and ensure timely access to treatment in order to reduce gastric cancer mortality. Future research should focus on evaluating public policies and their effectiveness in mitigating disparities in cancer outcomes.